Growth Performance of Native Hen at the Grower Phase (Aged 6-12 weeks) After Supplemented Arginine-Lysine in Low-Protein Fed - Onsalina Kemba; Charles V. Lisnahan; Agustinus A. Dethan (Journal of Tropical Animal Science and Technology, 2023)
This study aims to determine the growth performance of female Native chickens at the grower phase (6-12 Weeks) after being given arginine-lysine in low protein feed. This research was carried out from May to August 2022 at the Kampung Chicken Housing, Sion Women's Farmer Group, Sasi Village, Kefamenanu. The material used is 80 Native chickens aged 6-12 weeks with an average body weight of 400 g. The research method used is a complete randomized design. Chickens were randomly placed for 5 treatments and 4 replications, each replication consisted of 4 bird. The treatment given was P0 (control feed + 0.60% arginine + 0.52% lysine + 18% CP); P1 (control feed + 0.70% arginine + 0.61% lysine + 17% CP); P2 (control feed + 0.80% arginine + 0.70% lysine + 16% CP); P3 (control feed + 0.90% arginine + 0.79% lysine +15% CP); P4 (control feed + 1.00% arginine + 0.88% lysine + 14% CP). Variables observed were body weight gain, feed intake and feed conversion ratio. Data analysis using variance analysis and Duncan test. The results showed that the average body weight gain at treatments P0, P1, P2, P3 and P4 were 71.67±3.75; 84.69±3.55; 105.63±3.71; 105.46±7.15; and 94.38±3.50 g/bird/week, respectively. Feed intake were 277.41±15.95; 324.98±13.20; 401.13±15.10; 397.19±30.00; and 363.30±12.06 g/bird/week. Feed conversion ratio were 3.87±0.02; 3.84±0.01; 3.80±0.02; 3.77±0.03; and 3.85±0.01. Analysis of variance showed that the treatment had a significant effect on body weight gain, feed intake and feed conversion ratio of female Native chickens at the grower phase (P<0.05). It was concluded that the use of the arginine-lysine increases body weight gain, feed intake and decreases feed conversion ratio of female Native chickens at the grower phase (6 – 12 weeks). The level of 0.80-0.90% arginine + 0.70-0.79% lysine can streamline the use of feed crude protein by 2-3% from 18% to 15-16% and provide maximum results on the performance of female Native chickens at the grower phase.